The path to the reformed EU fiscal framework: A monetary policy perspective - Stephan Haroutunian; Krzysztof Bańkowski; Simeon Bischl; Othman Bouabdallah; Sebastian Hauptmeier; Nadine Leiner-Killinger; Marguerite O'Connell; I\~nigo Arruga Oleaga; Laurent Abraham; Agnieszka Trzcinska (European Central Bank (ECB), 2024)
This paper reviews the main arguments underpinning the reform of the EU's fiscal framework, which has culminated in the adoption by the EU legislators of a revised set of rules for the European economic governance including the Stability and Growth Pact (SGP). It takes a chronological approach by first discussing the Commission's legislative proposals of April 2023 against the pre-reform set of fiscal rules, before assessing the final political agreement which has materialised in the revised set of rules. In view of the multi-dimensional reform outcome, it is argued that the success of the reform of the fiscal framework will ultimately depend on its future implementation by the Commission and the Council. Combining the reform of the fiscal rules with better fiscal coordination through the establishment of a permanent euro area fiscal capacity was not proposed in the context of this reform. This paper argues that completing the architecture of Economic and Monetary Union (EMU) is an important missing element and should remain a policy priority.
Keywords: H6; H11; H50; 330; Fiscal rules; Stability and Growth Pact (SGP); Economic and Monetary Union (EMU)